The Resistance of Exotic Wheat Germplasm to Stripe Rust (Puccinia striiformis f. sp. tritici) under Nature Infection at Dera Ismail Khan, Pakistan: Wheat Germplasm Resistance to Stripe Rust Desease - Yaqoob, Muhammad (Biological Sciences - PJSIR, 2016)
An experiment comprising of 49 exotic wheat germ plasm accessions was conducted at Arid Zone Research Institute, Dera Ismail Khan, Pakistan under rainfed condition during 2013-14 for their resistance against stripe rust disease. The trial was laid out in randomised complete block design with three replications. All entries were planted in a four-row plot with 3 m for row length and 25 cm for space among rows. A local susceptible check was repeatedly sown after every 10 test entries. The crop was maintained under rainfed conditions. Results revealed that all the exotic genotypes were genetically divergent in response to stripe rust disease. The disease score ranged from very highly susceptible to very highly resistant. Among 49 exotic lines, 27 exhibited from very highly resistant while 10 were susceptible to very highly susceptible.